The Relationship Between Nursing Care Delivery Models, Emotional Exhaustion, and Quality of Nursing Care Among Jordanian Registered Nurses - Ammar Abusamra RN; Ahmad Hussien Rayan PhD; Rana F. Obeidat RN, CNS, PhD; Shaher H. Hamaideh PhD, MSc, RN; Manal Hassan Baqeas RN, PhD; Mohammed ALBashtawy PhD, MPH, RN (SAGE Publishing, 2022)
Background Inappropriately selected models of nursing care delivery and emotional exhaustion of nurses at work not only affect the nurses' health, but also the health of their patients. Purpose To examine the relationship between nursing care delivery models, nurses' emotional exhaustion, and quality of nursing care. Methods A cross-sectional survey that used a convenience sampling technique was employed. A total of 160 participants completed the study. Participants provided information about nursing care delivery models, nurses, emotional exhaustion, and quality of nursing care. Results Participants had a moderate level of emotional exhaustion. No statistically significant difference in the scores of quality of nursing care and emotional exhaustion were found according to the type of care delivery model ( P  > .05). Emotional exhaustion was significantly and negatively correlated with the (nursing staff characteristics) subscale of quality of nursing care ( r  = −.183, P  = .021). There was a significant difference in emotional exhaustion in regard to shift duty, marital status, education level, years of experience, salary, and working area). Only marital status significantly predicted emotional exhaustion ( t  = 2.57, B  = −8.98, P  = .011). Conclusions Quality of nursing care was associated with nurses' emotional exhaustion rather than models of nursing care delivery. As nurses' emotional exhaustion could negatively affect the quality of nursing care, addressing the emotional exhaustion of nurses is important to improve patient outcomes.